If a2 + b2 = 15 and ab = 3, then the value of (a-b)2 is:
A. 21 B. 18 C. 12 D. 9 E. 3
I really don't understand how I could possibly get this... can I please get some help?
please, help me I've been trying to figure this out for a while, but nothing works
suppose we expand (a-b)^2
(a-b)^ = a^2 + 2ab + b^2
= a^2 + b^2 + 2ab we know those..
= 15 + 2(3)
oh, okay! it took me a bit to comprehend what you did there, but now it really makes sense; before, I was confusing the 2 as multiplied by two instead of squaring, but thank you so much for helping me! :D